Clinical features, pathophysiology and management of fatal familial insomnia. (4th May 2017) - Redaelli, Veronica; Tagliavini, Fabrizio; Moda, Fabio
ABSTRACT: Introduction : Fatal Familial Insomnia (FFI) is an inherited prion disorder caused by a point mutation at codon 178 of the PRNP gene, resulting in aspartic acid to asparagine substitution (D178N) in coupling phase with methionine at position 129. The disease is associated with sleep alterations, autonomic dysfunctions, loss of weight and motor signs. After symptoms onset, the disease usually leads to death within 2 years and no treatments are available at present. Areas covered : This review focuses on classical and innovative aspects of FFI, with special emphasis on recent indications that infectious prion are not only confined to the central nervous system but can be detected in peripheral tissues of diseased patients. Expert opinion : Although FFI can be genetically diagnosed, the ability of innovative techniques to specifically detect minute amount of infectious prion in peripheral tissues (such as the olfactory mucosa) is of fundamental importance for disease monitoring and to evaluate the efficacy of specific treatments to interfere with disease progression. Overall, the ability of these techniques to mimic the process of prion propagation in vitro can be exploited to perform preliminary high throughput screenings of compounds in order to select the most effective for FFI treatment.